Limited Diversity - Business Models of German Cooperative Banks - Andreas Bley (Vierteljahrshefte zur Wirtschaftsforschung, 2018)
The structural diversity of the German banking market and the associated variety of business models is thought to have been an important factor in the stability of the German banking market in recent decades. This diversity is manifested both in the three-pillar structure of the German banking industry and within the pillars themselves. However, empirical analysis reveals that there is limited variety within the business models used by the German cooperative banks. Almost all cooperative banks concentrate on the lending and deposit-taking business with customers. Within the traditional business model, two different types of business can be identified, one of which is more focused on lending and the other on deposit-taking. – – Die strukturelle Vielfalt auf dem deutschen Bankenmarkt und die damit verbundene Vielfalt von Geschäftsmodellen dürfte in den vergangenen Jahrzehnten ein wichtiger Stabilitätsfaktor am deutschen Bankenmarkt gewesen sein. Diese Vielfalt zeigt sich zum einen in der 3-Säulen-Struktur der deutschen Kreditwirtschaft, zum anderen aber auch innerhalb der Säulen selbst. Für die deutschen Genossenschaftsbanken dokumentiert eine empirische Analyse eine begrenzte Vielfalt der Geschäftsmodelle. Fast alle Genossenschaftsbanken konzentrieren sich auf das Kredit- und Einlagengeschäft mit Kunden. Innerhalb des traditionellen Geschäftsmodells lassen sich zwei unterschiedliche Geschäftstypen identifizieren, von denen der eine stärker aktiv- und der andere stärker passivlastig ausfällt.
Keywords: G21; G32; P13; 330; German banking market; diversity; cooperative banks; business models; corporate governance